Protein composition of endurance trained human skeletal muscle - Reidy, P. T.; Hinkley, J. M.; Trappe, T. A.; Trappe, S. W.; Harber, M. P. (International Journal of Sports Medicine, 2014)
Evidence suggests that myofibers from endurance trained skeletal muscle display unique contractile parameters. However, the underlying mechanisms remain unclear. To further elucidate the influence of endurance training on myofiber contractile function, we examined factors that may impact myofilament interactions (i. e., water content, concentration of specific protein fractions, actin and myosin content) or directly modulate myosin heavy chain (MHC) function (i. e., myosin light chain (MLC) composition) in muscle biopsy samples from highly-trained competitive (RUN) and recreational (REC) runners. Muscle water content was lower (P<0.05) in RUN (73±1%) compared to REC (75±1%) and total muscle and myofibrillar protein concentration was higher (P<0.05) in RUN, which may indicate differences in myofilament spacing. Content of the primary contractile proteins, myosin (0.99±0.08 and 1.01±0.07 AU) and actin (1.33±0.09 and 1.27±0.09 AU) in addition to the myosin to actin ratio (0.75±0.04 and 0.80±0.06 AU) was not different between REC and RUN, respectively, when expressed relative to the amount of myofibrillar protein. At the single-fiber level, slow-twitch MHC I myofibers from RUN contained less (P<0.05) MLC 1 and greater (P<0.05) amounts of MLC 3 than REC, while MLC composition was similar in fast-twitch MHC IIa myofibers between REC and RUN. These data suggest that the distinctive myofiber contractile profile in highly-trained runners may be partially explained by differences in the content of the primary contractile proteins and provides unique insight into the modulation of contractile function with extreme loading patterns.